2011
DOI: 10.1111/j.1469-8137.2011.03813.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of a high-speed breeding technology to apple (Malus × domestica) based on transgenic early flowering plants and marker-assisted selection

Abstract: Summary• Breeding of apple (Malus · domestica) remains a slow process because of protracted generation cycles. Shortening the juvenile phase to achieve the introgression of traits from wild species into prebreeding material within a reasonable time frame is a great challenge.• In this study, we evaluated early flowering transgenic apple lines overexpressing the BpMADS4 gene of silver birch with regard to tree morphology in glasshouse conditions. Based on the results obtained, line T1190 was selected for furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
123
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 38 publications
1
123
0
6
Order By: Relevance
“…Arabidopsis flowering time genes Leafy (Schultz & Haughn 1991) and Flowering locus T (Blázquez & Weigel 1999) allow the hitherto most efficient early flowering induction in poplar (Weigel & Nilsson 1995, Rottmann et al 2000, Zhang et al 2010. Furthermore, it has been shown that transgenes can induce early flowering in trees more efficiently than cisgenes (Rottmann et al 2000, Zhang et al 2010, Flachowsky et al 2011, Tränkner et al 2010. Possibly, transgenes are less prone to "endogenous repressors" than cisgenes (Rottmann et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arabidopsis flowering time genes Leafy (Schultz & Haughn 1991) and Flowering locus T (Blázquez & Weigel 1999) allow the hitherto most efficient early flowering induction in poplar (Weigel & Nilsson 1995, Rottmann et al 2000, Zhang et al 2010. Furthermore, it has been shown that transgenes can induce early flowering in trees more efficiently than cisgenes (Rottmann et al 2000, Zhang et al 2010, Flachowsky et al 2011, Tränkner et al 2010. Possibly, transgenes are less prone to "endogenous repressors" than cisgenes (Rottmann et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…-Flachowsky et al 2007), but not in poplar (Hoenicka et al 2008). BpMADS4 transgenic lines are currently being used for apple breeding (Flachowsky et al 2011). The apple gene MdFT2, homologous of FT gene, promoted early flowering in apple and poplar (Tränkner et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las semillas obtenidas de las cruzas se tamizaron con marcadores moleculares y se cruzaron con germoplasma comercial, siempre monitoreados por diagnósticos moleculares de la presencia del locus responsable de dicha resistencia. De esta manera, fue posible combinar ese tipo de genes en tan solo tres años, cuando por el método tradicional se hubiesen requerido más de 10 y una población de plántulas mucho mayor (Flachowsky et al, 2011;Le Roux et al, 2012).…”
Section: Mejoramiento Biotecnológico Acelerado De áRbolesunclassified
“…El uso de potentes promotores constitutivos, como el del virus de mosaico de tabaco (35S), provoca la formación continua de flores que no son soportadas por la plántula y, como consecuencia, ocurre la caída de muchos frutos; también, se puede afectar la dominancia de crecimiento apical a favor de un mayor desarrollo de ramas y de un hábito de crecimiento tipo arbustivo (Flachowsky et al, 2011;Le Roux et al, 2012).…”
Section: Mejoramiento Biotecnológico Acelerado De áRbolesunclassified